Compact bandwidth-enhanced center-fed CPW zeroth-order resonant antenna loaded by parasitic element - Saravani S.; Chakrabarty C.K.; Din N.M. (Electromagnetics Academy, 2023)
Bandwidth; Efficiency; Polarization; Wireless telecommunication systems; Composite right/left-handed transmission lines; CST microwave studio; Dispersive behaviors; Full-wave simulations; Operational bandwidth; Polarization purity; Radiation efficiency; Wireless communication system; Antenna feeders